ON THE USE OF NEUROIMAGING STUDIES IN THE DIAGNOSIS OF ISCHEMIC STROKES - Nazarova, Zh.A.; Rakhmatova, S.N.; Bakhadirkhanov, M.M.; Abdurakhmonova, K.B. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To study the relationship of the clinical picture of ischemic stroke (II) and MRI in assessing changes in brain matter and cerebral hemodynamics. Material and methods: The study was conducted at the Department of Neurology in 2017-2019. 110 patients with II confirmed by MRI and clinically examined. Results: The presence of an extensive heart attack leads to complications and has an extremely poor prognosis. Significant criteria for the severity of the course of AI on MRI are pronounced perifocal edema, the detection of leukoaraosis, severe internal and external hydrocephalus. The combination of these signs gives reason to predict the worst outcome of ischemic stroke. So, with large infarct sizes with a morphologically significant defect, but without the presence of these three factors, positive clinical and neurological dynamics are more pronounced than in patients with smaller infarct sizes, but with the presence of these components. Conclusions: Changes in the venous blood circulation of the brain are detected on magnetic resonance imaging and magnetic resonance angiography and reveal a persistent reliable regular relationship with various brain conditions and carry important information about the organization of its blood supply and identification of the degree and severity of vascular brain damage.